Trypsin inhibitor in winged bean tuber (Psophocarpus tetragonolobus) and its inactivation by heat - Monserrate, Joji U.; del Valle, Mercedita (1978.)
The level of activity of trypsin inhibitors in winged bean (Psophocarpus tetragonolobus) tuber sand and the effect of heat on these inhibitors were determined using the benzoyl-OL-arginine-p-nitroanilide in HCl (BAPA-HCl) assay for trypsin. The average level of trypsin inhibitor activity in 6 month old tubers was calculated to be 6.39 TIU/mg. tuber while in 8 to 9 month old tubers, the activity was 18.04 TIU.mg. tuber. The trypsin inhibitor in 8 to 9 month old tubers was completely inactivated after 19 minutes of streaming at atmospheric pressure and 38 minutes of baking at 325°F.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Trypsin inhibitors; Winged bean